AB1193 An immune reference atlas from birth to adulthood identifies key developmental milestones. (12th June 2018) - Yeo, J.G.; Pan, L.; Arkachaisri, T.; Poh, S.L.; Ally, F.; Leong, J.; Yeo, K.T.; Pan, L.; Tan, A.Y.J.; Albani, S.
Abstract : Background: A developmental atlas of the immune system is key to understanding its normal maturation process and identifying the disease-associated cell subsets. The absence of a holistic developmental immune normogram is a critical unmet need. Objectives: To address this need and our hypothesis that age-related immune effector and regulatory cell subsets changes are present, we employ a multi-dimensional approach using mass cytometry to identify the cell subsets that shape the developing immune landscape from birth to adulthood. Methods: We interrogated the peripheral blood mononuclear cells from 126 healthy individuals (cord blood, newborn to adult) with mass cytometry using two extensive antibody panels embracing the most important cell lineages and their function. Quality control and batch effect correction were performed with outliers excluded before dimensional reduction and clustering to identify the unique immune cell subsets. Their frequencies across the age categories were presented as 3-D frequency histograms. Subsequent manual gating was done to further describe these immune cell subsets changes with age using Pearson correlation coefficient. Results: Distinct developmental gradients involving multiple effector and regulatory cell subsets shaped the maturing immune landscape. The naïve TNFα+CD4+T cells were enriched in the early childhood period and declined with age (Pearson correlation coefficient, r=−0.3503, p<0.001). In contrast, the memory TNFα+CD4+T cells increased with age (r=0.4149, p<0.0001). A transitional milestone from naive to memory TNFα+CD4+T cells was observed after 2 year old. This indicates that an intact CD4 +T cells TNFα effector mechanism is present at birth which progressively mature to involve the memory CD4 +T cells. For another cytokine IL17A, it was secreted solely by the memory CD4 +T cells with its population increasing with age (r=0.3753, p<0.001). Another distinct maturation milestone was observed in the naive CD8 +T cell subset where a transition from IL8 to IFNγ secretion after 10 year old was observed. The IL8 +and IFNγ+naive CD8+T cell subsets correlated negatively and positively with increasing age respectively (r=−0.2661, p<0.01 and r=0.2835, p<0.01). For the T regulatory cells, the age related changes were more gradual. The early thymic T regulatory cells (CD3+, CD4+, CD31+, CD45RA+, CD25+, Foxp3+, CD152+) demonstrated a gradual decline with age (r=−0.2966, p<0.01) while the memory T regulatory cells gradually increased with age (CD3+, CD4+, CD45RO+, CD25+, Foxp3+, CD152+) (r=0.2444, p<0.05). Conclusions: Key developmental milestones in the T cell compartment were identified and with the other subsets identified, a holistic description of the developing immune landscape was obtained. This atlas has the potential dual translational role of defining the stage of immune maturity and distilling the pathological cell subset in both paediatric and adult immune mediated diseases. The database and the related pipeline to analyse it will be provided as a free reference. Disclosure of Interest: None declared